Germany's Energiewende: A Tale of Increasing Costs and Decreasing Willingness-To-Pay - Mark A. Andor; Manuel Frondel; Colin Vance (RWI - Leibniz-Institut für Wirtschaftsforschung, 2016)
This paper presents evidence that the accumulating cost of Germany's ambitious plan to transform its system of energy provision - the so-called Energiewende - is butting up against consumers' willingness-to-pay (WTP) for it. Following a descriptive presentation that traces the German promotion of renewable energy technologies since 2000, we draw on two stated-preference surveys conducted in 2013 and 2015 that elicit the households' WTP for green electricity. Two models are estimated, one based on a closed-ended question framed around Germany's target of 35% renewable energy in electricity provision by 2020, and the other on an open-ended format that captures changes in WTP over time. To deal with the bias that typifies hypothetical responses, both models distinguish respondents according to whether they express definite certainty in their reported WTP. The results from both models reveal a strong contrast between the households' general acceptance of supporting renewable energy technologies and their own WTP for green electricity. – – Dieser Artikel vergleicht die wachsenden Kosten für die Energiewende mit der Zahlungsbereitschaft deutscher Haushalte für grünen Strom. Basierend auf zwei Erhebungen aus den Jahren 2013 und 2015 werden zwei Modelle geschätzt, die einerseits auf einer offenen Frage zur Zahlungsbereitschaft für die Erreichung des 35%-Ziels für das Jahr 2020 basieren und andererseits auf einer Frage mit fest vorgegebenen Werten für die Zahlungsbereitschaft. Unsere Ergebnisse zeigen einen starken Kontrast zwischen der generellen Befürwortung der Förderung erneuerbarer Energien und der Zahlungsbereitschaft für grünen Strom.
Keywords: D12; Q21; Q41; 330; certainty approach; energy policy; willingness-to-pay